2020
DOI: 10.18865/ed.30.2.277
|View full text |Cite
|
Sign up to set email alerts
|

Utilizing a Life Course Approach to Examine HI V Risk for Black Adolescent Girls and Young Adult Women in the United States: A Systematic Review of Recent Literature

Abstract: Objective: Black female youth have been disproportionately burdened by the HIV epidemic. Emerging literature suggests that individual and social-structural factors may uniquely increase HIV risk within this popu­lation during key developmental periods, namely adolescence (ages 10-17 years) and emerging adulthood (ages 18-25 years). Few studies, however, have compared drivers of risk within and between these key develop­mental periods. Therefore, we conducted a systematic review of recent literature to characte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 53 publications
0
14
1
Order By: Relevance
“…In a sample of sexual minority cisgender college students, identity affirmation moderated the link between victimization and depression, suggesting that the relationship between victimization and symptoms of depression depends on the amount of identity affirmation one receives (Busby et al, 2020). Moreover, identity affirmation has been associated with reduced substance use among TGD and cisgender youth (Hatchel & Marx, 2018; Taggart et al, 2020). Seeking and receiving gender affirmation from individuals and institutions can create a sense of acceptance and belonging from a young age, which should not be understated (Hatchel & Marx, 2018; Taggart et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…In a sample of sexual minority cisgender college students, identity affirmation moderated the link between victimization and depression, suggesting that the relationship between victimization and symptoms of depression depends on the amount of identity affirmation one receives (Busby et al, 2020). Moreover, identity affirmation has been associated with reduced substance use among TGD and cisgender youth (Hatchel & Marx, 2018; Taggart et al, 2020). Seeking and receiving gender affirmation from individuals and institutions can create a sense of acceptance and belonging from a young age, which should not be understated (Hatchel & Marx, 2018; Taggart et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…When parents communicate comprehensively with adolescents about sex, adolescents are likely to make healthy sexual decisions (for a review, see Coakley et al, 2017; Widman et al, 2016). Among Black girls, more frequent, open sexual communication is related to less sexual activity and more condom use (Donenberg et al, 2011; Taggart et al, 2020).…”
Section: Parental Sexual Communication and Monitoringmentioning
confidence: 99%
“…Specifically, additional work is needed among young Black women to better understand their interest and needs in relation to PrEP. Research to date highlights the multi-level factors influencing awareness and uptake of PrEP ( 16 ). In a recent qualitative study of young adult Black women in New York City, focus group participants identified cultural-environmental factors (e.g., a lack of information and resources to access PrEP), socio-normative factors (e.g., attitudes towards the long-term effects of PrEP and self-efficacy to follow the regimen), and proximal interpersonal factors (e.g., perceived HIV stigma from family and peers and a fear of rejection from partners) affecting PrEP awareness and uptake ( 17 ).…”
Section: Introductionmentioning
confidence: 99%